X-ray absorption spectroscopy and related techniques - Kodre, Alojz (Acta chimica slovenica, 2004)
In the extensive field of X-ray diagnostic techniques, nowadays mostly implemented on synchrotron X-ray sources, the X-ray absorption methods offer a relatively simple tool for structural analysis of materials. The advantage of the methods is the sensitivity to chemical species and the insensitivity to the long-range order. An overview of various detection techniques is given together with the discussion of accuracy of the method with regard to the spatial resolution and the possible contamination by intra-atomic contributions, the multielectron photoexcitations.
Keywords: rentgenska absorpcijska spektroskopija